Functional implications of Drosophila insulin-like peptides in metabolism, aging, and dietary restriction - kannan, Kavitha; Fridell, Yih-Woei (Frontiers in Physiology, 2013)
Abstract The neuroendocrine architecture and insulin/insulin-like signaling (IIS) events in Drosophila are remarkably conserved. As IIS pathway governs growth and development, metabolism, reproduction, stress response and longevity; temporal, spatial and nutrient regulation of dilps encoding Drosophila insulin-like peptides (DILPs) provides potential mechanisms in modulating IIS. Of eight DILPs (DILP1-8) identified, recent studies have furthered our understanding of physiological roles of DILP2, DILP3, DILP5 and DILP6 in metabolism, aging and responses to dietary restriction, which will be the focus of this review. While the DILP producing IPCs of the brain secrete DILP2, 3 and 5, fat body produces DILP6, identification of factors that influence dilp expression and DILP secretion has provided insight into the intricate regulatory mechanisms underlying transcriptional regulation of those genes and the activity of each peptide. Studies involving loss-of-function dilp mutations have defined the roles of DILP2 and DILP6 in carbohydrate and lipid metabolism respectively. While DILP3 has been implicated to modulate lipid metabolism, a metabolic role for DILP5 is yet to be determined. Loss of dilp2 or adult fat body specific expression of dilp6 has been shown to extend lifespan, establishing their roles in longevity regulation. The exact role of DILP3 in aging awaits further clarification. While DILP5 has been shown associated with dietary restriction (DR) mediated lifespan extension, contradictory evidence that precludes a direct involvement of DILP5 in DR exists. This review highlights recent findings on the importance of conserved DILPs in metabolic homeostasis, DR and aging, providing strong evidence for the use of DILPs in modeling metabolic disorders such as diabetes and hyperinsulinemia in the fly that could further our understanding of the underlying processes and identify therapeutic strategies to treat them.